Chamaecrista petiolata (Leguminosae, Caesalpinioideae), new species from Diamantina Plateau, Minas Gerais, Brazil - Cota, Matheus Martins Teixeira; Rando, Juliana Gastaldello; Mello-Silva, Renato (Phytotaxa, 2016)
During a floristic study of Chamaecrista in Diamantina plateau, Minas Gerais state, a new species was discovered. Chamaecrista petiolata is here described, illustrated, and compared to its putative closest relative species, C. catapodia and C. monticola. These species are shrubs, the stem-axis exceeding 1.5 m, and show sessile leaves, whereas C. petiolata is a subshrub up to 40 cm alt., with short petiolate leaves. The new species belongs to subsection Absus, which is characterized by glandular trichomes and lack of extrafloral nectaries.